PERTUMBUHAN PLANLET KRISAN (Dendranthema grandiflora Tzvelev) KULTIVAR PINK FIJI SETELAH PENAMBAHAN EKSTRAK TAUGE (Vigna radiata L.) PADA MEDIUM MURASHIGE DANSKOOG (MS) SECARA IN VITRO. - Nalindri Impitasari; Endang Nurcahyani; Tundjung Tripeni Handayani; Yulianty Yulianty (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2019)
Chrysanthemum (Dendranthema grandiflora Tzvelev) is one of the important ornamental plants in Indonesia and has high economic value . This plant is known as a producer of flowers with attractive shapes and colors . Seeing the magnitude of community interest and the potential utilization of chrysanthemum , causing this plant more and more developed and cultivated . This study aims to determine the concentration of optimum mungbean sprouts extract on the growth of chrysanthemum explants in vita . The addition of mungbean sprouts extracts (Vigna radiata L .) from concentration of 0% v/v , 2% v/v , 4% v/v , 6% v/v and 8% v/v on Murashige and Skoog(MS ) medium to growth eksplan Chrysanthemum (Dendranthema grandiflora Tzvelev ) Pink Fiji cultivars have been carried out in the tissue culture laboratory of Faculty of Mathematics and Natural Sciences , University of Lampung from November to December 2017 . This study used Completely Randomized Design (RAL ) 1 factor with 5 replications . Analysis of BNT variety and test is done at 5% level . The results showed that the extract from mungbean sprouts (Vigna radiata L . ) had no effect on plantlet height , number of shoot and number of chrysanthemum (Dendranthema grandiflora Tzvelev) plantlet leaves. The addition of mungbean spourts extracts on Murashige and skoog (MS) medium show 100% live plantlet.